Clinical outcomes of xenogeneic acellular dermal matrix combined with full-thickness skin graft in the eyelid reconstruction following the excision of eyelid malignant tumors - Xie, Linlin; Xie, Jing; Wang, Wei (Frontiers in Oncology, 2025)
ObjectiveThis study investigates the clinical efficacy of using the xenogeneic acellular dermal matrix (XADM) combined with full-thickness skin graft (FTSG) to reconstruct full-thickness eyelid defects following the excision of large malignant tumors.MethodsThis single-center retrospective observational study analyzed 21 patients who received XADM combined with FTSG for full-thickness eyelid defects reconstruction following tumor resection at our hospital between January 2020 and September 2022. The study was reported according to the STROBE statement reporting guidelines. The cases included 13 basal cell carcinomas, one meibomian gland carcinoma, and seven squamous cell carcinomas. In the first-stage surgery, XADM combined with a FTSG was used to reconstruct the full-thickness eyelid defect. In the postoperative, a pressure dressing was applied for 5 days removing stitches at 2 weeks. Repair outcomes were assessed at 1, 3, and 6 months postoperatively. At the 6 months postoperative follow-up, second-stage surgery was performed to separate the upper and lower eyelids, restoring normal eyelid anatomy and function.ResultsAt 2 weeks postoperatively, all graft marginal sutures were well-aligned, and no graft necrosis was observed after sutures were removed. No complications were found during the follow-up at 1 and 3 months postoperatively. At 6 months postoperatively, separation of upper and lower eyelid adhesions was performed. Slit-lamp examination post eyelid separation surgery reveals the overall healing outcome was satisfactory, with no significant inflammatory response or rejection observed. The overall healing outcome was satisfactory, with no significant inflammatory response or rejection observed. All 21 patients recovered well postoperatively. No significant complications were observed in any patient, with only one patient exhibiting mild lagophthalmos.ConclusionIn full-thickness eyelid reconstruction following the excision of eyelid malignant tumors, using XADM for reconstructing the posterior lamella and conjunctiva, combined with FTSG for repairing the eyelid skin and soft tissue, is a recommended approach.